Journeying beyond the gravity and interstellar space: Unveiling the Health Challenge in space missions – An extensive review - Chowdhury , Nishaat; Hisham Haras, Hibat Alla; Kumar, Naveen; Samuel, Vijay Paul; Sirasangandla, Srinivasa Rao (Bangladesh Journal of Medical Science, 2025)
Background Currently, space exploration and settlement are considered the future of humanity. It is significant to be aware of the risks and dangers that may arise and attentively plan the precautions before journeying to space. The effect of space stressors on humans is evolving research with implications for the future of space exploration and the wellbeing of astronauts. There have been space missions, and astronauts have taken initiatives to perform exercises and intense workouts to keep themselves healthy, but still, there were terrible consequences of prolonged exposure to the space environment. Therefore, the present review contemplates the short-term and long-term effects of space flights. This review also highlights that the well-being of astronauts or other personnel heading to space can lessen the long- and shortterm impacts of exposure to space stressors. It comprehends and analyzes the advancement of medical knowledge in the area of space medicine. Conclusion The challenges will always be there for someone accustomed to the earth’s atmosphere, but if these concerns are remembered and further research is conducted, would be beneficiary to the astronauts. Since the first space mission, the impacts of these pathological and physiological alterations have been recognized, even though the processes underlying them are unknown BJMS, Vol. 24 No. 03 July’25 Page : 906-915